Medical evidence of human rights violations against non-Arabic-speaking civilians in Darfur: a cross-sectional study. - Alexander C Tsai (Public Library of Science (PLoS), 2012)
Background Ongoing conflict in the Darfur region of Sudan has resulted in a severe humanitarian crisis. We sought to characterize the nature and geographic scope of allegations of human rights violations perpetrated against civilians in Darfur and to evaluate their consistency with medical examinations documented in patients' medical records. Methods and findings This was a retrospective review and analysis of medical records from all 325 patients seen for treatment from September 28, 2004, through December 31, 2006, at the Nyala-based Amel Centre for Treatment and Rehabilitation of Victims of Torture, the only dedicated local provider of free clinical and legal services to civilian victims of torture and other human rights violations in Darfur during this time period. Among 325 medical records identified and examined, 292 (89.8%) patients from 12 different non-Arabic-speaking tribes disclosed in the medical notes that they had been attacked by Government of Sudan (GoS) and/or Janjaweed forces. Attacks were reported in 23 different rural council areas throughout Darfur. Nearly all attacks (321 [98.8%]) were described as having occurred in the absence of active armed conflict between Janjaweed/GoS forces and rebel groups. The most common alleged abuses were beatings (161 [49.5%]), gunshot wounds (140 [43.1%]), destruction or theft of property (121 [37.2%]), involuntary detainment (97 [29.9%]), and being bound (64 [19.7%]). Approximately one-half (36 [49.3%]) of all women disclosed that they had been sexually assaulted, and one-half of sexual assaults were described as having occurred in close proximity to a camp for internally displaced persons. Among the 198 (60.9%) medical records that contained sufficient detail to enable the forensic medical reviewers to render an informed judgment, the signs and symptoms in all of the medical records were assessed to be consistent with, highly consistent with, or virtually diagnostic of the alleged abuses. Conclusions Allegations of widespread and sustained torture and other human rights violations by GoS and/or Janjaweed forces against non-Arabic-speaking civilians were corroborated by medical forensic review of medical records of patients seen at a local non-governmental provider of free clinical and legal services in Darfur. Limitations of this study were that patients seen in this clinic may not have been a representative sample of persons alleging abuse by Janjaweed/GoS forces, and that most delayed presenting for care. The quality of documentation was similar to that available in other conflict/post-conflict, resource-limited settings.